-6(x+1)+2(7x+9)=

Simple and best practice solution for -6(x+1)+2(7x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+1)+2(7x+9)= equation:


Simplifying
-6(x + 1) + 2(7x + 9) = 0

Reorder the terms:
-6(1 + x) + 2(7x + 9) = 0
(1 * -6 + x * -6) + 2(7x + 9) = 0
(-6 + -6x) + 2(7x + 9) = 0

Reorder the terms:
-6 + -6x + 2(9 + 7x) = 0
-6 + -6x + (9 * 2 + 7x * 2) = 0
-6 + -6x + (18 + 14x) = 0

Reorder the terms:
-6 + 18 + -6x + 14x = 0

Combine like terms: -6 + 18 = 12
12 + -6x + 14x = 0

Combine like terms: -6x + 14x = 8x
12 + 8x = 0

Solving
12 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 8x = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = 0 + -12
8x = 0 + -12

Combine like terms: 0 + -12 = -12
8x = -12

Divide each side by '8'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 2x+149=9x-5 | | 9-4(y+7)=7+3y | | x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 | | 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x | | -7(x+1)=2x-34 | | 24a-22=-4(1-6n) | | -x+3=-3x+11 | | 4x^2-48+44=0 | | x^2+36x=144 | | 6x-3=2x+5 | | 9x(3x)2x= | | 8x+9+2(10+x)=2x+29 | | 0.4x-0.6x-5=1 | | x=35 | | x^2+36x-144=0 | | -.33m-7=5 | | 26x-2-13x=10x+5+3x |

Equations solver categories